Corn Silk (Stigma maydis) Extract Successfully Reduces Blood Glucose Levels in Alloxan-Induced Diabetic Mice - Rachel Indah Putri Ayu Erlisna; Amanulloh Naufal Said; Anni Fithriyatul Mas'udah; Sugeng Mashudi (FORIKES, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder that requires effective therapeutic strategies with minimal adverse effects. The search for complementary antidiabetic agents derived from natural products has gained increasing attention, particularly those with potential antihyperglycemic activity and favorable safety profiles. Corn silk (Stigma maydis) contains bioactive compounds reported to influence glucose metabolism, making it a promising candidate for adjunctive therapy in T2DM management. This study aimed to evaluate the antihyperglycemic effect of the optimal dose of Stigma maydis ethanol extract (P3) compared with metformin (positive control, K+) in alloxan‑induced hyperglycemic male Swiss Webster mice. Male Swiss Webster mice were induced with alloxan at 150 mg/kgBW to establish a hyperglycemic model. The optimal dose of Stigma maydis extract (P3) and metformin (K+) were administered orally for 14 days. Blood glucose levels were measured before and after treatment. Paired t‑tests were used to assess within‑group changes, while independent t‑tests were applied to compare post‑treatment glucose levels between groups. The P3 group demonstrated a significant reduction in blood glucose levels (p = 0.003), with a post‑treatment mean of 111.40 mg/dL. Although the numerical decrease in the P3 group exceeded that of the metformin group, the difference between groups was not statistically significant (p = 0.576). These findings indicate that the antihyperglycemic activity of Stigma maydis extract is statistically comparable to metformin under the experimental conditions tested. In conclusion, the optimal dose of Stigma maydis ethanol extract produced a significant antihyperglycemic effect in alloxan‑induced mice, with efficacy comparable to metformin. These results support the potential of Stigma maydis as a complementary therapeutic option for T2DM management, warranting further investigation in larger preclinical and clinical studies.Keywords: Stigma maydis; metformin; antihyperglycemic activity